Pengaruh Pemberian Kukis Kombinasi Tepung Ikan Tongkol (Euthynnus affinis) dan Tepung Bayam (Amaranthus tricolor) Dengan Penambahan Probiotik Dadih Terhadap Kadar Feritin Serum Pada Tikus Wistar Anemia - Azahra, Azizah Firda; Lipoeto, Nur Indrawaty; Rofinda, Zelly Dia; Rita, Rauza Sukma; Desmawati, Desmawati; Yulia, Dwi; Fasrini, Ulya Uti (SENTRI: Jurnal Riset Ilmiah, 2025)
Anemia is a global health problem characterized by low hemoglobin and ferritin levels due to iron deficiency, which affects growth, cognition, and disease risk, particularly in children and women of reproductive age. Local food–based nutritional interventions such as skipjack tuna (heme iron), spinach (non-heme iron), and dadih (probiotics) have the potential to provide synergistic effects in improving iron status. This study aimed to determine the effect of cookies made from a combination of skipjack tuna flour and spinach with the addition of dadih probiotics on serum ferritin levels, as well as the effectiveness of Sodium Nitrite (NaNO₂) in decreasing ferritin and hemoglobin levels as indicators of anemia. The study used a Post-Test Only Control Group design with 36 female Wistar rats induced with anemia using NaNO₂ at a dose of 25 mg/200 g BW for 18 days, then divided into six treatment groups for 28 days. Ferritin levels were measured using the ELISA method. The results showed that administering cookies made from the combination of skipjack tuna flour and spinach with dadih probiotics significantly increased ferritin levels (P=0.000) compared to the control and single-ingredient groups. NaNO₂ was proven effective as an anemia-inducing agent. This combined cookie formulation has the potential to improve serum ferritin levels.